1998
DOI: 10.1002/(sici)1097-0134(19980501)31:2<214::aid-prot10>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Circular permutants in β-glucosidases (family 3) within a predicted double-domain topology that includes a (β/α)8-barrel

Abstract: By predicting the general secondary structure for beta-glucosidases (family 3), in conjunction with existing knowledge of the circular permutants present in B. fibrisolvens and R. albus, we were able to find the canonical elements of the secondary structure. The way these elements are linked suggests that there is a double-domain topology made up of a (beta/alpha)8-barrel domain and a "mainly all-beta" domain. A number of already known conserved motifs are located within (or near) the C-terminal part of the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The automatic procedure found most known CP relations, including those between plant lectins (Cunningham et al 1979), bacterial glucanases (Heinemann and Hahn 1995b), (β/α) 8 barrel proteins (Sergeev and Lee 1994; Jia et al 1996; Macgregor et al 1996; Garcia‐Vallve et al 1998), the C2 domain proteins (Nalefski and Falke 1996), ferredoxins (Jung and Lee 2000), flavin‐binding β‐barrel domains (Murzin 1998), the six‐stranded double‐ξ β‐barrels (Castillo et al 1999), and the DNA and other methyltransferases (Jeltsch 1999). Some new examples of CP‐related protein pairs are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The automatic procedure found most known CP relations, including those between plant lectins (Cunningham et al 1979), bacterial glucanases (Heinemann and Hahn 1995b), (β/α) 8 barrel proteins (Sergeev and Lee 1994; Jia et al 1996; Macgregor et al 1996; Garcia‐Vallve et al 1998), the C2 domain proteins (Nalefski and Falke 1996), ferredoxins (Jung and Lee 2000), flavin‐binding β‐barrel domains (Murzin 1998), the six‐stranded double‐ξ β‐barrels (Castillo et al 1999), and the DNA and other methyltransferases (Jeltsch 1999). Some new examples of CP‐related protein pairs are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Circularly permuted proteins occur also in nature. Lindqvist and Schneider (1997) reviewed some eight naturally circularly permuted proteins that were known by 1997, but at least six more (Garcia‐Vallve et al 1998; Murzin 1998; Castillo et al 1999; Jeltsch 1999; Polekhina et al 1999; Jung and Lee 2000) have been reported since then. Circularly permuted proteins can arise from a posttranslational modification (Carrington et al 1985; Bowles et al 1986), but a majority probably arose from gene duplication (Luger et al 1989; Ponting and Russell 1995; Jeltsch 1999) or exon shuffling (Doolittle 1987; Gilbert 1987) events.…”
mentioning
confidence: 99%
“…Computing similarity (or dissimilarity) between two strings is an important problem in general sequence analysis, 36–38 pattern recognition, 39,40 and biology. 41,42 The major computational tool used to study CPs is based on solutions to the circular pattern matching (CPM) problem.…”
Section: Background and Related Workmentioning
confidence: 99%
“…A number of studies have been reported on algorithms for detecting CPs for protein sequences. 41,42,50 The first method 51 used the dot matrix and human visualization to identify circular relationships between pairs of protein sequences. Altschul et al 52 used a dictionary method to find short fragments common to the protein sequence pairs and used human visualization to report the best local matches.…”
Section: Background and Related Workmentioning
confidence: 99%